Evaluasi Kesesuaian Layout Infrastruktur Tambak Bandeng (Chanos chanos) di Desa Lakekun Utara, Kecamatan Kobalima, Kabupaten Malaka - Frida Dos Santos; Franchy Ch Liufeto; Sunadji Sunadji (Nusa Cendana University, 2026)
Pond infrastructure layout is one of the key factors influencing the operational efficiency and productivity of milkfish (Chanos chanos) aquaculture. This study aimed to evaluate the suitability of the pond infrastructure layout in Lakekun Utara Village, Kobalima District, Malaka Regency, focusing on pond plot design, embankment construction, water channel systems, and overall pond layout. The study was conducted from May to October 2024 using a descriptive survey approach through field observations, interviews with pond farmers, and documentation. The collected data were analyzed descriptively by comparing the existing pond conditions with established technical principles for pond construction and management. The results showed that most pond plots were rectangular in shape, with sizes ranging from 60 × 25 m to 100 × 100 m. The embankments were generally constructed from sandy clay soil with heights ranging from 1.0 to 1.5 m; however, several embankments were insufficiently wide to support vehicle access during harvesting activities. The water management system had separate inlet and outlet channels, although some ponds still relied on mechanical pumps, resulting in higher operational costs. Furthermore, the existing pond layout had not fully supported efficient transportation of harvested fish. Therefore, improvements in pond plot dimensions, embankment width, gravity-based water channel systems, and transportation access are recommended to enhance operational efficiency and promote the sustainability of milkfish aquaculture. Keywords: infrastructure layout, milkfish pond, pond infrastructure, water channel system, Lakekun Utara Village.